ปัญหาการจัดดำเนินการโครงการเฝ้าระวังทันตสุขภาพ ในโรงเรียนประถมศึกษา สังกัดสำนักงานคณะกรรมการการศึกษาแห่งชาติ เขตการศึกษา 9 - สมพร ทองธวัช (จุฬาลงกรณ์มหาวิทยาลัย, 1995)
The purposes of this research were to study and to compare the problems of surveillance dental health program operation in elementary schools under the Jurisdiction of the Office of the National Primary education Commission, Educational Region Nine among different school sizes. The population were 400 school health teachers from 400 schools, 86 teachers from large size schools, 190 from medium size schools and 124 from small size schools. They were asked to respond to the questionnaires developed by the researcher. The mailed questionnaires of 361 (90.25%) were returned. The obtained data were then analyzed in terms of percentages. means, and standard deviations. On-Way analysis of Variance and the Scheffe method were employed to determine the significant differences at the .05 level. The findings revealed that : 1. Overall problems of surveillance dental health program operation in elementary schools under the Jurisdiction of the Office of the National Primary Education Commission, Education Region Nine were found to be in low level in all 5 areas. When considered in each items of all areas, 6 items of the problems were in high level. They were: 1) Lack of supervision from educators and dental officers. 2) No financial support from the Jurisdiction of the Office of the National Primary Education Commission to manage the tooth brush-tooth paste fund. 3) Not enough instructional media in dental health for schools. 4) Not enough supplementary reading books for students. 5) Students did not have their own personal tooth brush and cup. 6) Parents did not cooperate in participating of school surveillance dental health program. 2. The comparison of the problems of surveillance dental health program operation between large, medium, and small size schools were found to be statistically significant differences at the .05 level. Large size schools were found to have more problems than those of medium and small size schools. Medium size schools were found to have more problems than those of small size schools in managing, screening and recording the oral hygiene, and the correction of oral hygiene and dental health promotion.